Preliminary screening of nicotianamine synthase (nas) gene in sago palm using PCR technique - Rohana, Binti Muhammad. (Universiti Malaysia Sarawak (UNIMAS), 2005)
Nicotianamine synthase (nas) gene is a gene involved in iron-uptake mechanisms in plants. The isolation and understanding of the function of nicotianamine synthase gene in sago palm is essential for genetic manipulation of the plant in the future. In order to accomplish this, we attempted to screen two sets of primers designed from rice to look for possible nas in sago. CTAB method for miniprep extraction produced satisfactory results where DNA bands were observed in 1% agarose gel electrophoresis. Once the unpurified DNA was subjected for PCR with two sets of primers, a single band approximately 650bp was observed in one set of primers. Unfortunately, the cloning step could not be proceed due to time constrain.